Tudor and Stuart Britain 1485-1714 - Lockyer, Roger 1927-2017; Gaunt, Peter 1958- (Routledge, 2018)
"Henry VII's reign in 1485 to the death of Queen Anne in 1714, providing students and lecturers with a detailed chronological narrative of significant events, such as the Reformation, the nature of Tudor government, the English Civil War, the interregnum and the restoration of the monarchy. This fourth edition has been fully updated and is an excellent resource for both students and teachers of this period"...
Includes index
Keywords: Geschichte 1485-1714; Great Britain -- History -- Tudors, 1485-1603; Great Britain -- History -- Stuarts, 1603-1714; Großbritannien